PERSEPSI PENGELOLA USAHA MIKRO KECIL DAN MENENGAH (UMKM) TENTANG PENYAJIAN LAPORAN KEUANGAN BERBASIS SAK EMKM (STUDI KASUS PADA UMKM DI KOTA BENGKULU) - Sukma, Sukma; Desi Fitria (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to determine the perceptions of MSME managers in Teluk Segara, Kampung Melayu, and Ratu Samban Satu Districts of Bengkulu City regarding the presentation of financial reports based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The research method used is descriptive qualitative with data collection techniques through documentation and distribution of questionnaires to 35 respondents of MSMEs assisted by the Cooperatives and MSMEs Office of Bengkulu City. The results showed that of the 20 questions given, as many as 70% obtained an average score in the very good category, 15% good, and 15% quite good, so it can be concluded that the perception of MSME managers towards the presentation of financial reports based on SAK EMKM is classified as very good. Keywords: MSMEs, SME Financial Accounting Standards (SAK), Financial Reports, Perception, Descriptive Statistics